Wikileaks - Tosete, Francisco (Anuario ThinkEPI, 2011)
The organization Wikileaks delivered to five international media 250,000 cablegrams that had been sent by U.S. ambassadors in countries around the world to their government. After the media published those most relevant to public opinion, the organization was the subject of cyber attacks tomake it disappear. Likewise, the PayPal account (through which Wikileaks received donations) and the PostFinance bank account (where they maintained its activity) were cancelled. Also they were excluded from internet services like Amazon and were censored in Twitter. In response, a group of activists and hackers named Anonymous released coordinated attacks on MasterCard, Paypal and PostFinance bank on December 8.
Keywords: Wikileaks; Cablegate; Julian Assange; Amazon; Paypal; Mastercard; PostFinance; Anonymous; Cyberwar.